Friday

April 18, 2014

April 18, 2014

Posted by **michael** on Friday, April 22, 2011 at 5:42pm.

- mathematics -
**Ms. Sue**, Friday, April 22, 2011 at 5:51pm-8x/4=6-4x

-2x = 6 - 4x

2x = 6

x = ?

**Related Questions**

math - The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct? [(2x...

Algebra - Solve. 8x-(4x+5)=7 8x-1(4x+5)=7 8x-4x-5=7 4x-5+5=7+5 4x=12 x=3. Is ...

Mathematics - Evaluate 3 1/9 x (-3 3/5) ÷ 2 1/10 INTEGERS [3x(-3)-4x(-2)+5x2]+[-...

Math - Find the following function y=[(x-5)(4x+3)]^5 I arrived at 5(6x-2)[(x-5)(...

Math - For Reiny:What step did I do wrong.(Help) (x-4x^3)^2 =(x-4x^3)(x-4x^3)=(x...

algebra II - I would appreciate anyone's help in solving this problem.(1/4x^4+6...

Algebra 2 - Add. (1/4x^4+3/4x^3+7/8x^2+9)+(-3x^4+1/8x^2-9. Please help, this is...

Algebra 2 - Add. (1/4x^4+3/4x^3+7/8x^2+9)+(-3x^4+1/8x^2-9. Please help, this is...

Algebra 2 - Add. (1/4x^4+3/4x^3+7/8x^2+9)+(-3x^4+1/8x^2-9. Please help, this is...

Calculus - 22. Divide the expression before differentiating. F(x) = (8x^3 - 1...